A critical analysis of the distribution challenges and opportunities faced by South African independent documentary filmmakers - Grunenwald, Ryley (My University, 2014)
Distribution is one of the least theorised elements of film studies, yet its ability to monetise a film directly contributes to developing a sustainable film industry. This study analyses the distribution challenges and opportunities faced by South African independent documentary filmmakers. Ten South African documentary industry stakeholders participated in semi-structured “expert” interviews. Their responses were analysed using thematic encoding. Overall, the results indicate that the South African market is too small to support the South African documentary industry and that there is increasing pressure for documentary filmmakers to participate in the highly competitive international market. Furthermore, the results reveal that South African documentary filmmakers need to develop their business skills and have greater documentary-specific government support in order to maximise distribution opportunities and overcome distribution challenges both domestically and internationally. The analysis of findings, in which the results are interpreted in relation to existing literature, finds that South African documentary filmmakers are becoming less resistant to utilising the opportunities of international distribution and Video on Demand (VOD). However, they continue to face the challenge of negative international perceptions of Africa. Additionally, some filmmakers are using aspects of an alternative distribution model called hybrid distribution that Broderick (2009) theorised in response to shifting film market conditions. However, the study suggests that filmmakers need to amend new distribution models for South Africa’s unique distribution environment. Furthermore, the South African government’s development of a long-term vision for the South African documentary industry would help to maximise distribution opportunities, overcome distribution challenges and work towards a more sustainable industry.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, 2013